Psychometric Properties of the Persian Version of the Evidence-based Practice Implementation Questionnaire in Nurses - Ommolbanin Zare; Abbas Ebadi; Giti Ozgoli; Nourossadat Kariman (Journal of Holistic Nursing and Midwifery)
Introduction: In many healthcare centers, evidence-based practice (EBP) is a vital tool for providing better and safer healthcare services. Objective: This study investigates the psychometric properties of the Persian version of the EBP implementation questionnaire in nurses. Materials and Methods: This is a methodological and cross-sectional descriptive analytical study. We selected 400 nurses (200 for exploratory factor analysis and 200 for confirmatory factor analysis) via convenience sampling. The study questionnaire was translated based on the World Health Organization (WHO)’s guidelines. Construct validities of the EBP were assessed through exploratory and confirmatory factor analyses. The repeatability was also evaluated by the test re-test method. The study was conducted based on the COSMIN (consensus-based standards for the selection of health status measurement instruments) checklist. Results: The exploratory factor analysis revealed four factors: Evidence evaluation, development of evidence use, evidence sharing, and access to evidence. These factors could explain 58.30% of the total variance of evidence-based care in the nurses. Confirmatory factor analysis confirmed the goodness of fit of the 4-factor model of EBP implementation. The reliability of the evidence evaluation, development of evidence uses, evidence sharing, and access to evidence factors was confirmed using the Cronbach α coefficient. In addition, this questionnaire had excellenttest re-test reliability and the intra-class correlation coefficient (ICC), whose values were reported to be 0.996 with a confidence interval (CI) of 0.991 to 0.998 and P=0.001. Also, its re-test reliability was equal to 0.85. Conclusion: The Persian version of the EBP implementation scale has acceptable reliability and validity. In addition, the number of items in this questionnaire is low. Therefore, it can be used to measure the implementation of EBP in Iranian nurses and identify groups of nurses needing special interventions.